Renal function after intravitreal administration of vascular endothelial growth factor inhibitors in patients with diabetes and chronic kidney disease. Issue 4 (1st January 2018) - Kameda, Yusuke; Babazono, Tetsuya; Uchigata, Yasuko; Kitano, Shigehiko
Abstract: The present study aimed to determine whether intravitreal administration of vascular endothelial growth factor inhibitors is associated with deterioration of renal function, as seen with systemic administration, in patients with diabetes and chronic kidney disease. Estimated glomerular filtration rates before and after 160 intravitreal injections of vascular endothelial growth factor inhibitors (aflibercept, bevacizumab or ranibizumab) were compared in 69 patients with diabetes and with a baseline estimated glomerular filtration rate <60 mL/min/1.73 m 2 . We also determined the incidence of acute kidney injury. The data showed no significant difference in the estimated glomerular filtration rate before and after vascular endothelial growth factor inhibitor administration in all patients and in patient subgroups based on each inhibitor. Furthermore, no episodes of acute kidney injury occurred. In conclusion, intravitreal administration of vascular endothelial growth factor inhibitors is unlikely to be associated with a deterioration of renal function in patients with diabetes and chronic kidney disease. Abstract : This study aimed to determine whether intravitreal administration of vascular endothelial growth factor (VEGF) inhibitors is associated with deterioration of renal function, as is seen in systemic administration, in diabetic patients with chronic kidney disease. The results suggest that anti‐VEGF therapy in Ophthalmology hardly affected renal function even in these patients.